2012
DOI: 10.1002/ddr.21054
|View full text |Cite
|
Sign up to set email alerts
|

Tizanidine Increases Antinociceptive Effect and Prevents Gastric Damage Induced by Ketorolac in the Rat

Abstract: Ketorolac tromethamine is a nonsteroidal anti-inflammatory drug (NSAID) effective in the treatment of moderate to severe pain. Tizanidine, an a-2-adrenoceptor agonist with myospasmolytic action, is indicated for the treatment of back pain either as monotherapy or in combination with NSAIDs. However, side effects may limit their use. As both drugs produce side effects that are dose dependent, a combination of these drugs appears in order to reduce the dose required for efficacy and, consequently, side effects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Methyleugenol, diclofenac, and ketorolac administered individually herein produced dose-dependent antinociception (Figure 1B,D,F), in agreement with previous reports [16][17][18]. The results showed significantly reduced licking behavior time in phase II of the test.…”
Section: Discussionsupporting
confidence: 92%
“…Methyleugenol, diclofenac, and ketorolac administered individually herein produced dose-dependent antinociception (Figure 1B,D,F), in agreement with previous reports [16][17][18]. The results showed significantly reduced licking behavior time in phase II of the test.…”
Section: Discussionsupporting
confidence: 92%
“… 28 Rodriguez-Silverio et al observed the synergistic interaction between ketorolac and tizanidine in thermal hyperalgesia model and the gastroprotective activity of tizanidine against gastric damage induced by ketorolac in the rat. 29 …”
Section: Resultsmentioning
confidence: 99%
“…Studies in rats have shown that tizanidine could prevent the changes of glycoproteins in the gastric mucosa and gastric juice induced by NSAIDs, reduce central vagal activity and acid secretion, and increase mucosal blood flow by regulating central alpha-2-receptors. 29 , 50–52 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations